THE MEANING OF SYMBOLS IN BEAR BRAND MILK ADVERTISEMENTS (2021) - Najmi Hanifah Kamil; Juanda Juanda (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
This study analyzes the meaning of symbols in Bear Brand Milk Advertising (2021). The author aims to reveal the meaning of the symbols contained in the Bear Brand milk advertisement (2021). This study uses a qualitative method with a semiotic approach to the Roland Barthes model. Data were collected by analyzing sentences and visuals that appeared in Bear Brand's (2021) milk advertisements. There are two types of meaning, namely denotation and connotation contained in the sign of a black creature, a white dragon and a can of milk packaging contained in the Bear Brand (2021) milk advertisement. The sign serves as a bridge to represent the message that will be conveyed in Bear Brand dairy products. Keywords: Denotation, Conotation, signifier, signified